2014
DOI: 10.1088/2040-8978/16/10/105009
|View full text |Cite
|
Sign up to set email alerts
|

Engineering nonlinear response of nanomaterials using Fano resonances

Abstract: We show that, nonlinear optical processes of nanoparticles can be controlled by the presence of interactions with a molecule or a quantum dot. By choosing the appropriate level spacing for the quantum emitter, one can either suppress or enhance the nonlinear frequency conversion. We reveal the underlying mechanism for this effect, which is already observed in recent experiments: (i) Suppression occurs simply because transparency induced by Fano resonance does not allow an excitation at the converted frequency.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 77 publications
3
40
0
Order By: Relevance
“…In our theoretical and numerical studies using 3D simulations with retardation effects [23,26,28,29], we have demonstrated that path interference schemes can be adopted to gain control over the nonlinear frequency conversion processes emerging in plasmonic resonators. By appropriately choosing the level spacing of the quantum oscillator (i.e.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In our theoretical and numerical studies using 3D simulations with retardation effects [23,26,28,29], we have demonstrated that path interference schemes can be adopted to gain control over the nonlinear frequency conversion processes emerging in plasmonic resonators. By appropriately choosing the level spacing of the quantum oscillator (i.e.…”
Section: Introductionmentioning
confidence: 91%
“…In two recent theoretical works [26,28] 3D boundary element method (MNPBEM [31]) simulations demonstrate that second harmonic generation in plasmonic resonators can be enhanced by using the Fano resonances. In these simulations, the retardation effects are taken into account, where it is confirmed that the retardation effects do not play a significant role on the existence of SHG enhancement.…”
Section: Theory and Simulationsmentioning
confidence: 99%
See 3 more Smart Citations